HUBUNGAN STATUS GIZI DENGAN VIRAL LOAD PADA MONITORING TERAPI ANTIRETROVIRAL ODHA DI PELAYANAN KESEHATAN PERAWATAN, DUKUNGAN DAN PENGOBATAN KABUPATEN BANDUNG TAHUN 2023 - suryamah, Yeni; Septiriani, Oka; Puspitasari, Khalina (Jurnal Sehat Masada, 2024)
Human Immunodeficiency Virus (HIV) infection is a health and social problem in Indonesia. To date, the best treatment for HIV patients is combination antiretroviral (ARV) treatment. Nutritional status is one of the important factors that influence the success of ARV therapy because it is related to the body's immune response to ARV therapy. The purpose of this study was to determine the relationship between nutritional status and viral load in monitoring ARV therapy. The research design used was a retrospective cohort study with a sample of 116 people living with HIV AIDS (PLWHA). Data analysis was performed using logistic regression analysis method. It was found that the majority of respondents were <40 years old (77%), male (79%), did not have TB infection (65%), had a drug compliance rate >95% (53%), BMI ≥18.5 kg/m2 (59%) and had a suppressed viral load (84%). The results showed no significant association between nutritional status and viral load after controlling for other covariate variables, namely TB infection and adherence (p-value=0.134). Nevertheless, nutritional status and HIV infection are highly correlated, so routine monitoring is still needed in addition to viral load, such as weight, height when PLWHA visit health care facilities, and efforts are also needed to provide additional food to keep PLWHA's BMI from decreasing.